1995
DOI: 10.1002/pros.2990260308
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prostate specific antigen, prostate specific membrane antigen, and LNCaP‐based enzyme‐linked immunosorbent assays in prostatic cancer patients and patients with benign prostatic enlargement

Abstract: Serum assays for prostate specific antigen (PSA; monoclonal), for prostate specific membrane antigen (PSM; Western blot), and a LNCaP/7E11.C5-based competitive enzyme-linked immunosorbent assay (ELISA) were evaluated in a small number of prostate cancer patients with localized or disseminated disease, and judged to be in clinical progression or remission based on National Prostate Cancer Project (NPCP) criteria. PSA values recognized the presence of clinical progression in localized disease (B1-C) and to a les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 3 publications
0
25
0
2
Order By: Relevance
“…These findings differ from serum studies in which elevated concentration of PSM and PSA indicated surgical treatment failure. 5,10,11 Individual cells in poorly differentiated carcinoma produce less PSA than cells in well differentiated and moderately differentiated carcinoma, but usually are present in such large numbers (greater tumor volume) and replace more of the prostate that serum PSA concentration is higher. Given the greater expresssion of PSM per cancer cell with increasing grade, we expect greater amplification of serum concentration with this marker than with PSA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings differ from serum studies in which elevated concentration of PSM and PSA indicated surgical treatment failure. 5,10,11 Individual cells in poorly differentiated carcinoma produce less PSA than cells in well differentiated and moderately differentiated carcinoma, but usually are present in such large numbers (greater tumor volume) and replace more of the prostate that serum PSA concentration is higher. Given the greater expresssion of PSM per cancer cell with increasing grade, we expect greater amplification of serum concentration with this marker than with PSA.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate, PSMA appeared to be downregulated in benign prostatic hyperplasia (BPH) and overexpressed in poorly differentiated primary tumors, with the highest expression in bone and lymph node metastatic prostate carcinomas, especially in patients who relapsed after androgen deprivation therapy (6,10,11). Besides its expression in prostate tissue, PSMA was also detected in body fluids, i.e., serum and seminal plasma by Western blot analysis, with the highest level in patients with late-stage prostate cancer (4,(12)(13)(14). These results suggest that PSMA activity is inversely correlated with androgen 1 This study was supported in part by grants from the National Cancer Institute (CA85067), the Virginia Prostate Center, and Cytogen Corporation.…”
mentioning
confidence: 99%
“…PSA has proven to be a valuable marker for prostatic cancer, both in the early detection and screening, as well as post-treatment follow-up [4,9,10]. However, because PSA is not a prostate cancer specific protein, considerable overlap exists between the levels of the serum PSA concentration in patients with benign prostatic enlargement and those in prostate cancer patients [11].…”
Section: Discussionmentioning
confidence: 99%